Intervertebral Disc Degeneration and Low Back Pain Depends on Duration and Magnitude of Axial Compression. (29th April 2022) - Li, Jitian; Ma, Yan; Jiao, Yucheng; Xu, Libo; Luo, Yage; Zheng, Jiancheng; Zhang, Xingkai; Chen, Zhe
Abstract : Purpose . The pathological role of axial stress in intervertebral disc degeneration (IDD) is controversial, and there was no quantified study until now. Here, we tried to clarify the correlation between IDD or low back pain (LBP) and axial stress at different duration and magnitude in vitro and in vivo. Method . In vitro, the gene expression of aggrecan, matrix metalloproteinase-3 (MMP3), calcitonin gene-related peptide (CGRP), and substance P (SP) was measured when nucleus pulposus cells (NPCs) were compressed under gradual severity. In vivo, a measurable Ilizarov-type compression apparatus was established for single coccygeal (Co) intervertebral disc (IVD) compression of Co7-8 in mouse. Gradient stress was placed at 0.4 Mpa (mild), 0.8 Mpa (moderate), and 1.2 Mpa (severe) for three days to investigate the effect of the magnitude of axial stress. Additionally, mild compression with 3, 7, and 14 days was used to determine the effect of the duration of axial stress. Subsequently, we evaluated the severity of IDD and LBP by radiological X-ray film; histological examination with H&E staining; immunohistochemical analysis with collagen II, aggrecan, and CGRP staining; and western blot analysis with collagen II, aggrecan, MMP-3, and interleukin-1 β (IL-1 β ). Results . When NPCs suffered gradual increased mechanical stress, the cells exhibited gradual downregulated expression of extracellular matrix (ECM)-related gene of aggrecan, upregulated expression of IDD-related gene of MMP3, and LBP-related gene of CGRP and SP. In the meantime, with different magnitudes of axial stress, the IVD showed progressively severe IDD and LBP, with gradual narrowing intervertebral height, destruction of IVD anatomy, decreased ECM, and increased catabolic factors and proalgesic peptides. Conclusion . Axial compression is one of the critical pathological factors to cause IDD and LBP, and there was a strong positive correlation depended on the duration and magnitude of compression.